Strengthening Public Trust and Citizen Engagement Through E-Government Application Innovation: The Intervening Role of E-Government Effectiveness In Medan City - Jonson Rajagukguk; Vera Asihna Riris Pasaribu; Maringan Panjaitan (ARRUS Journal of Social Sciences and Humanities, 2026)
This study aims to examine the influence of E-Government application innovation on public trust and citizen engagement through E-Government effectiveness as an intervening variable in Medan City. The study is motivated by the continuing reliance on manual public service systems, which often create administrative delays, limited accessibility, low transparency, and insufficient citizen participation. In response to these challenges, E-Government application innovation is expected to strengthen digital public service delivery by improving service availability, accessibility, transparency, operational efficiency, and public participation. This study employs a descriptive quantitative approach using Structural Equation Modeling (SEM). The population consists of 2,494,512 residents of Medan City in 2023, and the sample comprises 100 respondents selected using stratified random sampling based on educational level. The results show that all measurement indicators satisfy convergent validity, discriminant validity, and composite reliability requirements. The hypothesis testing results indicate that E-Government application innovation has a significant effect on public trust, citizen engagement, and E-Government effectiveness. Furthermore, E-Government effectiveness significantly influences public trust and citizen engagement. The indirect effect analysis also confirms that E-Government effectiveness plays an intervening role in strengthening the influence of E-Government application innovation on both public trust and citizen engagement. These findings suggest that innovative and effective E-Government applications are essential for building citizen confidence, encouraging public participation, and improving the quality of digital public services in Medan City.